Effect of Marketing Knowledge Competency and Entrepreneurship Orientation on Marketing Capabilities and Marketing Performance of Fishery Smes in Malang City, East Java - Nur Azizah Charir; Mimit Primyastanto; Zainal Abidin (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Fishery SMEs of in Malang city is increasing, these SMEs owner face up the challenge of confronting competitor’s product. Fishery SMEs can improve their competitiveness through marketing knowledge competency, entrepreneurial orientation (EO) and need to grow the marketing capabilities and improving marketing performance. This study aimed to analyze the effect of marketing knowledge competency on marketing capabilities, EO on marketing capabilities, marketing knowledge competency on marketing performance, EO on marketing performance, and marketing capability on marketing performance. This research used SEM (Structural Equation Modelling) with WarpPLS 3.0 approach. Population in this research were owner fishery SMEs as much as 304 owners in Malang City. Samples taken by proportionate random sampling technique. This research was conducted by spreading quetionnaires to 115 owners of fishery SMEs in Malang City. These results showed that marketing knowledge competency has positive and significant effect on marketing capabilities, EO has positive and significant effect on marketing capabilities, marketing knowledge competency has positive and significant effect on marketing performance, EO has positive and significant effect on marketing performance, and marketing capabilities has positive and significant effect on marketing performance. We recommend that the owners of fishery SMEs tp improve the EO and marketing capabilities to result good marketing performance. However, marketing competency knowledge should also be maintained.